Prevalence, Risk Factors and Effects of Low Back Pain on Quality of Life among Healthcare Professionals of Lahore, Pakistan: Effects of Low Back Pain on Quality of Life - Rafique, Nigarish; Farooq, Waqas; Umer, Zartash; Tariq, Fatima; Bukht, Rameen; Zeeshan, Muhammad; Rukh, Mah; Zakar, Rubeena; Saleem, Javeria (Pakistan Journal of Health Sciences, 2023)
Low back pain being a prevalent disease is affecting the quality of life. The health care professionals also experience low back pain due to their nature of work. Objective: To determine the prevalence of low back pain with its contributing factors and its impact on life’s quality of healthcare professionals. Methods: The cross-sectional study design was applied to conduct this study. In this study, a total of 384 health care professionals from different hospitals of Lahore, Pakistan were randomly surveyed. Descriptive statistics and Chi square test used to analyze the data (p-value < 0.05). Results: The frequency of pain in lower back was 63% among health care professionals. A total of 56% female healthcare professionals had low back pain. Risk factors i.e. smoking behavior, poor posture at work, standing time, working hour per day, sleeping disorder and general stress had significant association with pain intensity rating scale (p-value < 0.005). The quality of life of healthcare professionals measured with Oswestry disability index (ODI) had also significant relation with low back pain (p-value < 0.0). Conclusions: In conclusion, the pain in lower back was more prevalent in female healthcare professionals. Occupational risk factors, Smoking behavior, sleeping disorder and general stress were considered as major risk factors. The most useful coping strategy was rest. The quality of life of healthcare professionals were highly effected by low back pain.